Religion and economic prosperity: help or hindrance? (Religion y prosperidad economica: ¿ayuda u obstáculo?) - Orłowski, Piotr (Cauriensia, 2023)
In the contemporary description of the impact of religiosity on social life, the dominant view is one dating back to Max Weber (+1920) on the importance of the Protestant ethic, which, while emphasizing the value of work, at the same time favors prosperity, seeing it as a sign of God's blessing. Based on these assumptions, some seem to suggest that Protestants earn more because their religiosity translates directly into increased profits in their professional work. Contemporary Polish economic philosophers Marcin Gorazda and Tomasz Kwarcinski seem to argue with this thesis in their latest book "Between Prosperity and Happiness." (Cracow 2020). In my paper, I will refer to a brief outline of the biblical context of the question of the propriety of wealth, the reasons for the New Testament warnings against the dangers of wealth, in order to refer to research highlighting the relationship between religiosity and economic success (for example, recent American research on the impact of religion on family firms). Thus, the thesis of Protestantism's favorability toward wealth (compared to Catholicism) must take into account other still other factors such as demographic or sociological.